(untitled) (Journal of Civil Engineering Researchers, 2025)
Although currently, a large part of the existing buildings are considered inefficient in terms of energy, the ability to save energy consumption up to 80% has been proven in residential and commercial buildings. This study aims to calculate energy consumption during the operational phase caused by various scenarios of thermal insulation combinations in a building’s exterior shell. The simulation was conducted using Design Builder software, with a five-story residential building in Tehran as the case study. Initially, the building was modeled in Design Builder, and keeping all other characteristics constant, ten scenarios were defined: nine using different types of thermal insulation and one without insulation. The software outputs for each scenario were analyzed. Results showed that the best thermal insulation layer is polyurethane foam, which saves 1070.15 kilowatt-hours of energy during one year of the building’s operation. This article can help designers and construction engineers optimize the energy consumption of buildings by deciding the right materials. © 2017 Journals-Researchers. All rights reserved